2015
DOI: 10.1371/journal.pone.0143413
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Nonmetastatic Melanoma B (Gpnmb)-Positive Macrophages Contribute to the Balance between Fibrosis and Fibrolysis during the Repair of Acute Liver Injury in Mice

Abstract: Background and aimsGlycoprotein nonmetastatic melanoma B (Gpnmb), a transmembrane glycoprotein that is expressed in macrophages, negatively regulates inflammation. We have reported that Gpnmb is strongly expressed in the livers of rats fed a choline-deficient, L-amino acid-defined (CDAA) diet. However, the role of macrophage-expressed Gpnmb in liver injury is still unknown. This study aimed to clarify the characteristics of infiltrating macrophages that express Gpnmb, and the involvement of Gpnmb in the repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…6. MMP9 up‐regulation was significantly attenuated in the GPNMB Mut mice, which is in good agreement with literature showing that GPNMB up‐regulates MMP9 (3, 41, 42). In contrast, TIMP‐1 expression was not significantly different between the strains.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…6. MMP9 up‐regulation was significantly attenuated in the GPNMB Mut mice, which is in good agreement with literature showing that GPNMB up‐regulates MMP9 (3, 41, 42). In contrast, TIMP‐1 expression was not significantly different between the strains.…”
Section: Resultssupporting
confidence: 92%
“…However, inherent differences in the models used, peritoneal macrophage reaction to LPS injection, and autoimmune reactions compared with our MI model might explain these outcomes. Other researchers could not reproduce the anti‐inflammatory role of GPNMB or assign other primary functions to GPNMB expressed in macro‐phages (11, 16, 42, 45). Although GPNMB is a regulator of inflammation in some diseases, its inflammatory function is not responsible for the GPNMB effects we observed in the infarcted heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that Gpnmb expressed in macrophages functions as a feedback regulator of pro-inflammatory responses [20]. In CCl4-induced acute liver injury, Gpnmb is expressed in infiltrating hepatic macrophage and modulate the balance between fibrosis and fibrolysis [14]. Medeleine et al reported that increased Gpnmb expression was observed in monocyte and macrophages from uremic (the end-stage renal disease) patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gpnmb transgenic rats that over-express Gpnmb in liver cells showed that Gpnmb attenuates the development of hepatic fibrosis [13]. Gpnmb-positive macrophages infiltrate the liver during the recovery phase of CCl4-induced acute liver injury and contribute to the balance between fibrosis and fibrolysis in the repair process following acute liver injury [14]. Thus, it seems that Gpnmb may promote proliferation and differentiation and inhibit immunocyte activation, inflammation and fibrosis.…”
Section: Introductionmentioning
confidence: 99%